2004
DOI: 10.1002/polb.20034
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influence of the morphology and capillary rheological properties in nylon/glass‐fiber/liquid‐crystalline‐polymer blends

Abstract: Nylon‐6/glass‐fiber (GF)/liquid‐crystalline‐polymer (LCP) ternary blends with different viscosity ratios were prepared with three kinds of nylon‐6 with different viscosities as matrices. The rheological behaviors of these blends were characterized with capillary rheometry. The morphology was observed with scanning electron microscopy and polarizing optical microscopy. This study showed that although LCP did not fibrillate in binary nylon‐6/LCP blends, LCP fibrillated to a large aspect ratio in some ternary ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…In comparison to the phenomenon described before [20], the bigger the initial size of LCP droplets, the easier the fibrillation of LCP was.…”
Section: Initial Size Of Lcp Dropletsmentioning
confidence: 86%
See 2 more Smart Citations
“…In comparison to the phenomenon described before [20], the bigger the initial size of LCP droplets, the easier the fibrillation of LCP was.…”
Section: Initial Size Of Lcp Dropletsmentioning
confidence: 86%
“…The most substantial decrease in viscosity does not correlate directly with the onset of fibrillation, because the latter also depends on the LCP concentration and the deformation of LCP droplets from spheres to fibrils. Due to this competition, the viscosity decrease of highly-filled ternary blends is mainly resulted from the lubrication of LCP droplets [20]. The viscosity of N/GB1/LCP 34/55/11 lower than that of N/GB/LCP 84/5/11 (Fig.…”
Section: Capillary Number and Critical Capillary Number In Shear And mentioning
confidence: 98%
See 1 more Smart Citation
“…[9] Surprisingly, it was found that the addition of glass fiber significantly reduced the melt viscosity of PA6/LCP blends. This effect was so marked that some PA6/GF/LCP composites had a quite low viscosity, not only lower than neat PA6, Morphology of ternary N/GB/LCP composites with different GB contents at shear rate of 115 s À1 (LCP content is 11 wt %).…”
Section: Rheological Hybrid Effectmentioning
confidence: 97%
“…Except for the abovediscussed factors, the geometrical factor in these multi-phase systems also had its influence. It included the size of temporarily formed capillaries in fiber-filled melts [8,9] and the size of gaps between nearby rotating spheres. [14,15] It was the prerequisite for the hydrodynamic driving force to act.…”
mentioning
confidence: 99%